VEGETATIVE GROWTH OF TOMATO (Lycopersicum esculentum Mill.) INFLUENCED BY AERATED COMPOST TEA (ACT) FROM BROMELAIN LITTER INDUCED BY LIGNINOLITIC Trichoderma sp. - Bambang Irawan; Salman Farisi; Yulianty; Sela Habibu Rohmah (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2021)
The pineapple waste increased by the rise of production in pineapple, one of increasing pineapple waste is pineapple pulp (bromelain litter). The bromelain litter will be disadvantage for the environment, this matter could be solved by converting bromelain litter into compost. The composting process in this study used ligninolytic fungus (Trichoderma sp.). Composting technology which currently has rapidly developed is Aerated Compost Tea (ACT) or a derivate product of compost. The use of this study was to ensure the best incubation period of ACT bromelain litter which induced by Trichoderma sp. fungus on the growth of tomato (L. esculentum Mill.). The study was conducted using a completely randomized design (CRD) with 7 treatments and 3 replications, namely: P0= control (without ACT), P1= ACT bromelain 24 hours, P2= ACT bromelain 48 hours, P3= ACT bromelain 72 hours, P4= ACT bromelain and leaf litter 24 hours, P5= ACT bromelain and leaf litter 48 hours, and P6= ACT bromelain and leaf litter 72 hours. The variables observed were number of leaves and plant chlorophyll content. The data obtained were analyzed with ANOVA at the level of 5 % and tested for the Least Significant Difference (LSD) at the level of 5 %. The results of this study showed that ACT was induced by Trichoderma sp. fungus which effective for the vegetative growth of tomato (L. esculentum Mill.) is ACT bromelain litter with incubation period up to 72 hours (P3).